Formula călinesciană a parabolei – Șun sau calea neturburată. Mit mongol - Simona (Revista de Istorie și Teorie Literară)
In the play entitled Șun sau calea neturburată. Mit mongol/ Shun or the Undisturbed Path.A Mongolian Myth, the formula of the literary parable points out not only the mechanisms of reloading the specific semantic structures of parable itself – starting from the author’s own reflections on the impact of an enlightened or philosopher prince on people’s destiny –, it also generates a unique mirror effect on the other writings of the literary critic. Our approach proposes a critical evaluation of these aspects so as to define a viable innovative re-reading perspective on a text placed in the shadow of some more critically valued writings created by G. Călinescu.